J. M. KEYNES AND HIS ECONOMIC THEORY: AN ETHICAL PERSPECTIVE - S. N. Ivaskovsky (Vestnik MGIMO-Universiteta)
The article examines the philosophical and moral foundations of the biggest economist and political philosopher of the 20th century John Maynard Keynes (1883-1946), who played an important role in rethinking a number of important provisions of the classical political economy and in creating the ideological and methodological basis of the "Keynesian revolution" and of the new field of economic analysis-macroeconomics. The author traces the main stages in the formation of ethical views of Keynes, shows that his interest in ethics as the system of values in society was dictated by the need for the new conceptual vision of economic realities and by the search of an answer to the main ethical question: "What should we do?". Attention is drawn to the fact that an understanding of the ethical orientation of economic theory by Keynes allowed him to take a critical stance towards traditional individualism and Victorian morality of thrift and moneymaking and to conclude that rational and "right" forms of individual behaviour are not a guarantee of the prosperity of society as a whole. To achieve the latter Keynes justified the necessity of "central control" by the State of the overall level of aggregate expenditure. It isstressed that the ethical views of Keynes correspond with the concept of the "ethic of responsibility"- a relatively new scientific discipline, which originated as a response to the risks of technogenic era: pollution, resource constraints, overpopulation, lack of stability of the world economy. The final part of the article analyzes one of the most important, from the point of view of Keynes, vices of capitalism - reckless proclivity of people to the multiplication of "abstract monetary wealth". It is shown that it doesn't only disfigure the psyche and consciousness of people, but also changes the direction of development of the market economy towards "speculative capitalism", which creates a threat to civilization, creativity, well-being and full development of the individual.